2020
DOI: 10.36108/laujoces/0202/40(0110)
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Flexible Pavement Failure along Ede – Akoda Road, Osun State, Southwestern Nigeria

Abstract: Ede to Akoda is a trunk B-road built over 30 years ago. It has been in despicable condition leading to fatal accidents and loss of life and properties that impacted negatively on the community. This study investigated the flexible pavement failure along the road in order to ascertain the possible causes of its failure. The methodology adopted covered reconnaissance survey, assessment of the physical condition of the road and soil investigation of subgrade. The result of reconnaissance survey revealed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Underfunding of tertiary institutions is one of the major reasons of industrial strike by the academic staff union of universities. This underfunding is as a result of bad governance where public treasury is looted instead of utilizing the money for public bene t which is in line with the ndings of [29]. Other limiting factors comprised improper supervision, errors in detailing and construction, poor workmanship, wrong speci cation of materials and out-of-stock materials due to dynamism of the building industry.…”
Section: Constraints Of Building Maintenance In the Institutionsmentioning
confidence: 91%
“…Underfunding of tertiary institutions is one of the major reasons of industrial strike by the academic staff union of universities. This underfunding is as a result of bad governance where public treasury is looted instead of utilizing the money for public bene t which is in line with the ndings of [29]. Other limiting factors comprised improper supervision, errors in detailing and construction, poor workmanship, wrong speci cation of materials and out-of-stock materials due to dynamism of the building industry.…”
Section: Constraints Of Building Maintenance In the Institutionsmentioning
confidence: 91%
“…Studies by [9,10,11] suggested that these frequent flexible pavement failures are certainly a function of poor design. Amongst the several potential causes of flexible pavement failure, [7, 12,13] concluded that poor drainage was the main culprit. Timely rehabilitation of flexible pavements, however, can save overall maintenance costs by over 50% [14].…”
Section: Introductionmentioning
confidence: 99%